A phylogenomic approach reveals a low somatic mutation rate in a long-lived plant. Issue 1922 (11th March 2020) - Orr, Adam J.; Padovan, Amanda; Kainer, David; Külheim, Carsten; Bromham, Lindell; Bustos-Segura, Carlos; Foley, William; Haff, Tonya; Hsieh, Ji-Fan; Morales-Suarez, Alejandro; Cartwright, Reed A.; Lanfear, Robert
Abstract : Somatic mutations can have important effects on the life history, ecology, and evolution of plants, but the rate at which they accumulate is poorly understood and difficult to measure directly. Here, we develop a method to measure somatic mutations in individual plants and use it to estimate the somatic mutation rate in a large, long-lived, phenotypically mosaic Eucalyptus melliodora tree. Despite being 100 times larger than Arabidopsis, this tree has a per-generation mutation rate only ten times greater, which suggests that this species may have evolved mechanisms to reduce the mutation rate per unit of growth. This adds to a growing body of evidence that illuminates the correlated evolutionary shifts in mutation rate and life history in plants.